EMBR-11. SYNERGISTIC DRUG COMBINATIONS FOR THE TREATMENT OF MYC AMPLIFIED GROUP 3 MEDULLOBLASTOMA. (1st June 2021) - Zeuner, Simon; Vollmer, Johanna; Peterziel, Heike; Sigaud, Romain; Oppermann, Sina; ElHarouni, Dina; Hielscher, Thomas; Witt, Olaf; Oehme, Ina; Milde, Till; Ecker, Jonas
Abstract: Background: Medulloblastoma (MB) is a highly aggressive brain tumour in children. Patients with Group 3 MB harbouring a MYC -amplification (subtype II) show a particularly poor outcome despite high-intensity multimodal therapy. We and others have previously shown that MYC amplified Group 3 MB cells are highly susceptible towards treatment with class I histone deacetylase (HDAC) inhibitors such as entinostat. However, in clinical trials HDACi as a monotherapy show only modest efficacy in solid tumours. We propose to increase the efficacy of class I HDACi by drug combinations. Methods: To identify synergistic drug combinations (entinostat + X) for the treatment of MYC amplified MB we performed a drug screen with a library of n=75 clinically available compounds as single agents and in combination with entinostat in n=3 MYC amplified vs. n=1 MYC -non amplified cell lines. Synergistic behaviour of the six most promising drug combinations was validated by metabolic activity assays, cell count experiments and gene expression profiling. Synergy was assessed by the Loewe additivity model using a combination of ray design and checkerboard matrix. Results: The drug screen revealed n=20/75 drugs that were particularly effective (drug sensitivity score ≥10) in combination with entinostat treatment in all three MYC amplified cell lines. Synergy assessment of the top n=6 drugs confirmed strong synergistic activity with entinostat for n=2 drugs (navitoclax, irinotecan). The BCL-2 family inhibitor navitoclax showed the most robust synergy with entinostat in subsequent validation experiments. Conclusion: Several drugs either clinically available or currently in clinical trials, including the BCL-2/Xl/w inhibitor navitoclax, show promising effects in a combination therapy with entinostat for the treatment of MYC amplified Group 3 MB.